2x+9x-4=9x+3

Simple and best practice solution for 2x+9x-4=9x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+9x-4=9x+3 equation:



2x+9x-4=9x+3
We move all terms to the left:
2x+9x-4-(9x+3)=0
We add all the numbers together, and all the variables
11x-(9x+3)-4=0
We get rid of parentheses
11x-9x-3-4=0
We add all the numbers together, and all the variables
2x-7=0
We move all terms containing x to the left, all other terms to the right
2x=7
x=7/2
x=3+1/2

See similar equations:

| 7(x+1)=-3x-11 | | 10x+(-20)=30 | | 23+6x=-43 | | |3x-1|+2=5 | | 6x^2=94 | | -2a+3=-7-a | | 9=m-0.007 | | 10x+-20=30 | | 7(-40+3x)=-238 | | -6+2m=0 | | -x+5=7x-3 | | 7x+7=-3x-11 | | 6+3+n=19 | | |1/2x-1|=5 | | -3x-14=-50 | | 2(0)+1y=8 | | -1=n/3-4 | | c+6=7+9 | | 16+3×5+2x=5(x–1) | | 8^x/2=4^x+1 | | 8.7=n-1.4 | | -9-y=-1 | | 8.7=r−1.48.7=r-1.4 | | 1/2x-11=2/3x+12 | | 75=n+1275=n+12 | | 7=-3/2x+1 | | 1/10(3x-40)=4/5x-5 | | 6-2((x)/(3))=1+4x | | X-7=6x+8 | | 6-2(x/3)=1|4x | | 8x+(24+4x)=360 | | -3/5x+-3=3 |

Equations solver categories